Pivotal Advance: Invariant NKT cells reduce accumulation of inflammatory monocytes in the lungs and decrease immune-pathology during severe influenza A virus infection. - Kok, W; Denney, L; Benam, K; Cole, S; Clelland, C; Mcmichael, A; Ho, L (2012)
Little is known of how a strong immune response in the lungs is regulated to minimize tissue injury during severe influenza A virus (IAV) infection. Here, using a model of lethal, high-pathogenicity IAV infection, we first show that Ly6C(hi)Ly6G(-) inflammatory monocytes, and not neutrophils, are the main infiltrate in lungs of WT mice. Mice devoid of iNKT cells (Jα18(-/-) mice) have increased levels of inflammatory monocytes, which correlated with increased lung injury and mortality (but not viral load). Activation of iNKT cells correlated with reduction of MCP-1 levels and improved outcome. iNKT cells were able to selectively lyse infected, MCP-1-producing monocytes in vitro, in a CD1d-dependent process. Our study provides a detailed profile and kinetics of innate immune cells in the lungs during severe IAV infection, highlighting inflammatory monocytes as the major infiltrate and identifying a role for iNKT cells in control of these cells and lung immune-pathology.